0930 The Impact Of Nightmares On Emotion Dysregulation In Veterans With And Without Posttraumatic Stress Disorder. (27th April 2018) - Cipollone, G; Barilla, H; Brownlow, J A; Cobb Scott, J; Ross, R; Gur, R C; Kling, M; Bhatnagar, S; Gehrman, P
Abstract: Introduction: Recurrent nightmares and disrupted rapid eye movement (REM) sleep are both core features of posttraumatic stress disorder (PTSD), the latter showing association with increased irritability and agitation. Less is known, however, about the relation of nightmares per se to emotional impairment. The present study assessed the role of nightmares and objectively measured sleep in emotion dysregulation in Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF) Veterans with and without PTSD. Methods: Thirty combat-exposed OEF/OIF Veterans (PTSD, n=20; non-PTSD control, n=10) were participants in a study examining neurobiological and neuropsychological factors associated with PTSD. Veterans' PTSD symptomatology was assessed using PTSD Checklist-Military Version (PCL-M), and Nightmare-Effects Survey (NES). Veterans also completed the Beck Depression Inventory (BDI). Laboratory polysomnograms were examined for sleep continuity and sleep architecture (total sleep time (TST); stages N1, N2, and N3 sleep; and REM sleep). The associations among nightmare severity and other variables were examined using correlational and regression analyses. Results: Analyses revealed that Veterans who reported greater impact of nightmares on their daily functioning, as assessed by the NES, exhibited greater irritability and agitation. REM sleep percent was added to the model but it was not significantly related to NES scores. Conclusion: Findings indicate that the impact of nightmares on daytime emotion regulation is not related to specific abnormalities of REM sleep. As is the case for insomnia, it may be aspects of the sleep disturbance other than objective EEG-based abnormalities that are more strongly associated to emotional dysregulation. Support (If Any): This work was funded by the Defense Advanced Research Projects Agency under a grant from the US Army Research Office (grant number W911NF1010093).